1960
DOI: 10.1084/jem.112.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Immune Cellular Injury

Abstract: It was demonstrated in the preceding paper (1) that incubation of primary isolates of normal human amnion cells with specific rabbit antibody and normal human serum resulted in immune cellular injury as measured by two independent criteria of cytotoxicity. It was further shown that the factors in normal human serum which were required in addition to specific antibody for production of cytotoxicity were indistinguishable from components of hemolytic complement and calcium and magnesium ions. Thus, no fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1961
1961
1969
1969

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…from its naturally occurring proenzyme to the active enzyme, C~I esterase (5). They are str~Mngly similar to current observations on the role of complement in immune cytotoxlcity, studies in which the deleterious effects of complement on human amnion cells in the presence of specific antibody were initiated by C'I esterase (17,21). They are also similar to the data previously reported on the sequence of events in complement fixation by antigen-antibody aggregates (5).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…from its naturally occurring proenzyme to the active enzyme, C~I esterase (5). They are str~Mngly similar to current observations on the role of complement in immune cytotoxlcity, studies in which the deleterious effects of complement on human amnion cells in the presence of specific antibody were initiated by C'I esterase (17,21). They are also similar to the data previously reported on the sequence of events in complement fixation by antigen-antibody aggregates (5).…”
Section: Discussionsupporting
confidence: 88%
“…The observations on the effect of inhibitor in the D-L reaction were therefore similar to other studies on the role of inhibitor in complement fixation (22) and immune cytotoxicity (21).…”
Section: Discussionsupporting
confidence: 88%
“…In view of the lack of penetration of antibodies into living cells, the ability of trypsinized cell suspensions to absorb out cytotoxic activity from Hashimoto serum also argues for combination occurring at the cell surface. Previous studies on immune cytolysis with other cell systems such as HeLa cells (18,19), and immune hemolysis (20), have emphasized the importance of cell surface interactions with the antibody. Electron microscope studies using ferritin-labeled antibody to HeLa cells (21), have shown that antibody combination is restricted to the cell surface until after the addition of complement, when binding to the subcellular elements of the cytoplasm can be observed after rupture of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ross & Lepow (25,26) have studied this same general mechanism of cell injury further and have implicated the C1 esterases in the cytotoxic reaction. They have also established the importance of calcium and magnesium in this immune reaction, and they have worked out the critical sequence in which the multiple reactions, involving each of the components of complement, must take place.…”
Section: Tumor Cells and Antibodies Directed Against Themmentioning
confidence: 99%